2001
DOI: 10.1097/00042737-200102000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of clinical and radiological features at diagnosis of achalasia during a 19-year period in central France

Abstract: Despite a smaller oesophageal diameter at the time of diagnosis, during the period 1994-1998, diagnostic delay was not reduced. No clinical features associated with late diagnoses could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…The prevalence of advanced ME in IdAc in our study was similar to the prevalence reported by D'Alteroche and coworkers (24%, n = 248) 15 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The prevalence of advanced ME in IdAc in our study was similar to the prevalence reported by D'Alteroche and coworkers (24%, n = 248) 15 …”
Section: Discussionsupporting
confidence: 92%
“…The esophageal diameter was the only factor influenced by the diagnostic delay in his study ( P = 0.0001), i.e. the increase in the diagnostic delay was followed by the increase in the degree of ME, result consistent with our findings 15 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…d'Alteroche et al estimated the evolution of clinical and radiologic features of a large population of achalasic patients. 10 Dysphagia, chest pain, and heartburn were more frequent in young patients. Women had 1.7 times the risk of men for suffering of chest pain and 2.2 times the risk for heartburn.…”
Section: Introductionmentioning
confidence: 97%